Learners’ Misconceptions and Errors when Solving Inequalities - Paul Mutodi; Mogege Mosimege; Kgaladi Maphutha (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This study explored Grade 12 learners’ misconceptions and errors when solving inequalities. A test on Inequalities was administered to a randomly selected sample of 50 Grade 12 learners in Sekhukhune District, South Africa. A rubric was used to guide the assessment and scoring of learners’ scripts. Ten (10) learners were purposively selected based their test responses for interviews to explain their errors, misconceptions and reasoning. Results indicated that learners’ errors are due to misunderstandings from prior learning and insufficient mathematical content knowledge. Misconceptions and errors recorded from learners’ work include: learners solved inequalities as equations, treated inequality signs as an equal sign, and multiplying both sides of inequalities involving fractions by a variable. Learners had challenges in presenting solutions of inequalities using graphical and number lines. The study recommends that teachers should make an effort to understand learners’ thought processes and use this understanding to anticipate learners’ misconceptions and errors and prescribe remediation corrective strategies.